Efficacy of fine needle aspiration cytology in the early diagnosis of different head and neck malignancies: a hospital based prospective study - Chowdhury, Bonapart (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Fine needle aspiration cytology (FNAC) is a very useful diagnostic modality for early diagnosis of cancers in the head and neck region where large majority of the lesions are in the form of cervical lymphadenopathy, thus FNAC is easily feasible. This can be used as a significant screening tool if sensitivity is found to be high. Methods: A hospital based prospective study to find the accuracy of FNAC in correctly diagnosing malignant lesions in patients with visible or palpable mass lesions in the head and neck area where both FNAC and histopathological examination (HPE) is possible taking HPE as gold standard. Results: FNAC is a very effective tool in the early diagnosis of different head and neck malignancies with sensitivity of 91.37% and specificity of 97.62%. Conclusions: FNAC is a simple, quick and safe diagnostic modality for different head and neck malignancies with significant sensitivity and specificity, thus can be used as a screening tool effectively.